Impact of LPG promotion program in Ghana: The role of distance to refill - Adjei-Mantey, K.; Takeuchi, K.; Quartey, P. (Energy Policy, 2021)
This study investigates the impact of a clean cooking intervention on primary fuel choice and on households’ willingness to pay for an improved LPG distribution model in Ghana. Using data obtained via a survey of 904 households in two beneficiary districts, we found that the intervention led to higher LPG usage. The program increases the probability of households choosing LPG as a primary cooking fuel by 24% and the rate of use of LPG among households by 33%. Furthermore, an analysis of willingness to pay shows that delivery preference is not statistically different between beneficiary and control groups. The distance to refill the cylinder significantly affects LPG usage and willingness to pay. A policy that brings LPG refill closer to households and reduces the time and money cost of accessing a refill station is key to increasing the adoption of LPG as the primary cooking fuel.
Research Article
Keywords: LPG; Refill station; Willingness to pay; Distance; Ghana; RLPGPP